Pregnancy-specific stress, fetoplacental haemodynamics, and neonatal outcomes in women with small for gestational age pregnancies: a secondary analysis of the multicentre Prospective Observational Trial to Optimise Paediatric Health in Intrauterine Growth Restriction. Issue 6 (21st June 2017) - Levine, Terri A; Grunau, Ruth E; Segurado, Ricardo; Daly, Sean; Geary, Michael P; Kennelly, Mairead M; O'Donoghue, Keelin; Hunter, Alyson; Morrison, John J; Burke, Gerard; Dicker, Patrick; Tully, Elizabeth C; et al.
Abstract : Objectives: To examine associations between maternal pregnancy-specific stress and umbilical (UA PI) and middle cerebral artery pulsatility indices (MCA PI), cerebroplacental ratio, absent end diastolic flow (AEDF), birthweight, prematurity, neonatal intensive care unit admission and adverse obstetric outcomes in women with small for gestational age pregnancies. It was hypothesised that maternal pregnancy-specific stress would be associated with fetoplacental haemodynamics and neonatal outcomes. Design: This is a secondary analysis of data collected for a large-scale prospective observational study. Setting: This study was conducted in the seven major obstetric hospitals in Ireland and Northern Ireland. Participants: Participants included 331 women who participated in the Prospective Observational Trial to Optimise Paediatric Health in Intrauterine Growth Restriction. Women with singleton pregnancies between 24 and 36 weeks gestation, estimated fetal weight <10th percentile and no major structural or chromosomal abnormalities were included. Primary and secondary outcome measures: Serial Doppler ultrasound examinations of the umbilical and middle cerebral arteries between 20 and 42 weeks gestation, Pregnancy Distress Questionnaire (PDQ) scores between 23 and 40 weeks gestation and neonatal outcomes. Results: Concerns about physical symptoms and body image at 35–40 weeks were associated with lower odds of abnormal UAPI (OR 0.826, 95% CI 0.696 to 0.979, p=0.028). PDQ score (OR 1.073, 95% CI 1.012 to 1.137, p=0.017), concerns about birth and the baby (OR 1.143, 95% CI 1.037 to 1.260, p=0.007) and concerns about physical symptoms and body image (OR 1.283, 95% CI 1.070 to 1.538, p=0.007) at 29–34 weeks were associated with higher odds of abnormal MCA PI. Concerns about birth and the baby at 29–34 weeks (OR 1.202, 95% CI 1.018 to 1.421, p=0.030) were associated with higher odds of AEDF. Concerns about physical symptoms and body image at 35–40 weeks were associated with decreased odds of neonatal intensive care unit admission (OR 0.635, 95% CI 0.435 to 0.927, p=0.019). Conclusions: These findings suggest that fetoplacental haemodynamics may be a mechanistic link between maternal prenatal stress and fetal and neonatal well-being, but additional research is required.